Africa 11 - Lukacs, Stefan (NonPlus Filmproduction, 2008)
Verzio FF Submission Emmanuel Ekeigwe is an immigrant of Nigerian descent. Having arrived in Austria in 2001 the former professional football player immediately decided to go about pursuing his beloved profession and try his luck in Viennese soccer. His initial enthusiasm was soon dampened by encounters with native soccer players and their reservations about people of other skin color. After several rejections Emanuel Ekeigwe decided to found his own soccer team, solely for African immigrants: the New African Football Academy (NAFA).“Africa 11” is an on-site inspection of one of Central Europe's most highly innovative projects in the area of the integration of foreign asylum seekers.